An imperfect maintenance policy for mission-oriented systems subject to degradation and external shocks - Liu, Bin; Xie, Min; Xu, Zhengguo; Kuo, Way (Computers & industrial engineering, 2016)
•The mission-oriented system is subject to both degradation and external shocks.•Maintenance actions can only be implemented after a mission is completed.•Reliability model and maintenance model are formulated for mission-oriented system.•Optimal maintenance strategy is obtained by minimizing the long-run cost rate.•Numerical results show that mission duration has significant impact on maintenance schedule. This paper develops a maintenance model for mission-oriented systems subject to natural degradation and external shocks. For mission-oriented systems which are used to perform safety-critical tasks, maintenance actions need to satisfy a range of constraints such as availability/reliability, maintenance duration and the opportunity of maintenance. Additionally, in developing maintenance policy, one needs to consider the natural degradation due to aging and wearing along with the external shocks due to variations of the operating environment. In this paper, the natural degradation is modeled as a Wiener process and the arrival of random shock as a homogeneous Poisson process. The damage caused by shocks is integrated into the degradation process, according to the cumulative shock model. Improvement factor model is used to characterize the impact of maintenance actions on system restoration. Optimal maintenance policy is obtained by minimizing the long-run cost rate. Finally, an example of subsea blowout preventer system is presented to illustrate the effectiveness of the proposed model.